2020
DOI: 10.1021/acs.jpcc.0c01614
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Mechanisms of Ultralarge Bending Deformation of Single-Crystalline TiO2–B Nanowires

Abstract: Titanium dioxide (TiO 2 ) nanowires (NWs) are usually considered to be brittle semiconductor materials, which limits their use in strain-related applications, even though they are already widely applied in various fields. Based on observations using an in situ transmission electron microscopy method, we find, for the first time, that individual crystalline TiO 2 NWs with a bronze phase (TiO 2 −B) can exhibit an ultralarge elastic bending strain of up to 18.7%. Using an in situ atomic-scale study, the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The SF formation, together with the nucleation and glide of the extended dislocations, offers the NWs an ability to accommodate large bending deformations. Our previous works showed that TiO 2 NWs with a pure bronze phase or an anatase/bronze dual-phase could withstand bending strains larger than 10%, largely contributed by rich dislocation movements on the {11̅1}, {100}, and {001} planes in a bronze TiO 2 crystal. , However, the fracture strains of rutile TiO 2 NWs are much smaller than those of the two kinds of TiO 2 NWs, probably because the rutile TiO 2 NWs lack the nucleation and movements of perfect dislocations belonging to other slip systems. Previous work reported that, at high temperature and higher stress conditions, barriers of {110}⟨001⟩ could be overcome by cross-slip, leading to the nucleation and movement of {110}⟨001⟩-type full dislocations. , Since half-dislocations on {101̅} planes can lower the Peierls–Nabarro stress hindering dislocation motion, dissociation of dislocations belonging to {101̅}⟨101⟩ is more likely to occur than the full dislocation slip.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The SF formation, together with the nucleation and glide of the extended dislocations, offers the NWs an ability to accommodate large bending deformations. Our previous works showed that TiO 2 NWs with a pure bronze phase or an anatase/bronze dual-phase could withstand bending strains larger than 10%, largely contributed by rich dislocation movements on the {11̅1}, {100}, and {001} planes in a bronze TiO 2 crystal. , However, the fracture strains of rutile TiO 2 NWs are much smaller than those of the two kinds of TiO 2 NWs, probably because the rutile TiO 2 NWs lack the nucleation and movements of perfect dislocations belonging to other slip systems. Previous work reported that, at high temperature and higher stress conditions, barriers of {110}⟨001⟩ could be overcome by cross-slip, leading to the nucleation and movement of {110}⟨001⟩-type full dislocations. , Since half-dislocations on {101̅} planes can lower the Peierls–Nabarro stress hindering dislocation motion, dissociation of dislocations belonging to {101̅}⟨101⟩ is more likely to occur than the full dislocation slip.…”
Section: Resultsmentioning
confidence: 99%
“…4 Nanomaterials have a large fraction of atoms residing at or near the surface due to their enormous surface-to-volume ratio, likely resulting in different deformation mechanisms from their bulk counterparts. 5 Many kinds of ceramic nanowires (NWs), such as diamond, 6−8 Si, 9,10 and titanium dioxides (TiO 2 ), 11,12 have been experimentally found to demonstrate large deformations due to the occurrence of dislocation nucleation and movements, deformation twinning, lattice shearing, and others. TiO 2 NWs are attractive in fundamental research and various applications, such as photoelectronics, 13 biomatrixes, 14 and nanoelectrical−mechanical systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations